IoT-Based Child Tracking System using Blynk - Hani Farhanah Hasbullah,; Shamsul Mohamad, (Evolution in Electrical and Electronic Engineering, 2024)
Children are on the rise and victims of crime in today's world. Due to the number of schoolchildren in crime cases, parents are now more worried about their children while they are away from home. This initiative was developed to assist parents in keeping an eye on their kids at all times, especially when they're in public. Once the child presses the button when they are in danger, the device can track their location and an alarm will sound via the buzzer.  In Blynk applications, it can also send notifications to the parent's smartphone. Blynk functions very well when the notifications are sent to the parent’s smartphone in just 1.33 seconds on average. In the meantime, when the button was pressed, the buzzer made a sound. The buzzer's sound is strong enough to alarm other people nearby. The coordinates that the child sends to the Blynk when the button is pressed also display the child's precise location.